2020
DOI: 10.1200/op.20.00105
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Cancer Recurrence in Patients With Localized Renal Cell Carcinoma

Abstract: PURPOSE: Patients with cancer commonly report distress and fear of cancer recurrence (FCR) impacting quality of life and clinical outcomes. This study aims to test the association between emotional well-being and clinical characteristics of survivors with localized renal cell carcinoma (RCC). MATERIALS AND METHODS: Survivors with localized RCC were invited to participate in this study through social media by the Kidney Cancer Research Alliance. Participants self-reported clinical characteristics, distress (Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 32 publications
4
18
1
Order By: Relevance
“…In a complementary study, Decat Bergerot et al, reported that younger, female patients had an increased fear of cancer recurrence [167].…”
Section: Discussionmentioning
confidence: 98%
“…In a complementary study, Decat Bergerot et al, reported that younger, female patients had an increased fear of cancer recurrence [167].…”
Section: Discussionmentioning
confidence: 98%
“…With the rise of novel targeted‐ and immuno‐therapy regimens, urologists and oncologist also need to learn how to capture, treat and monitor new side‐effects associated with these treatments (Grimm et al, 2010). In addition, especially female and young RCC cancer survivors experience clinically relevant fear of cancer recurrence (Bergerot et al, 2020). These psychological comorbidities impose a significant impact on the health‐related quality of life after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of cancer survivors experience clinically significant FCR [ 3 , 4 ], which is associated with psychological distress, poorer quality of life (QoL) and greater healthcare use [ 1 , 5 ]. FCR is more prevalent amongst survivors who are female [ 1 , 4 , 6 ] and younger [ 1 , 4 , 6 ] and experience physical symptoms [ 1 , 7 9 ]. If untreated, FCR can persist for many years, highlighting the need for intervention [ 1 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%